Central Limit Theorem for Linear Eigenvalue Statistics of Orthogonally Invariant Matrix Models - Shcherbina, M. (Журнал математической физики, анализа, геометрии, 2008)
We prove central limit theorem for linear eigenvalue statistics of orthogonally invariant ensembles of random matrices with one interval limiting spectrum. We consider ensembles with real analytic potentials and test functions with two bounded derivatives.